The fentanyl crisis & the dark side of social media. (December 2019) - Al-Rawi, Ahmed
Highlights: Purpose: This study examines the opioid crisis and we argue here that social media platforms including some mobile communication apps can be regarded as Dark Social Networking Sites (DSNS). Design/methodology/approach: The study's sample includes a unique dataset of over 6 million tweets and Instagram posts referencing fentanyl including 5687 messages (856 tweets and 4831 Instagram posts) that promoted fentanyl sale and provided some instructions on where and how to purchase it. Findings: Opioid drug dealers spam users and specify different geographical locations, most of which are in the United States. They also provide potential buyers with different guidelines on how to exchange contact information, using a variety of encrypted means such as mobile communication apps especially WhatsApp and Wickr to guarantee secure transactions. Practical implications: The study has several implications including the examination of how fentanyl sale is promoted on social media, offering also insight into some ways to identify opioid drug sales. Originality/value: Fentanyl sale is often promoted on social media, but there is very little empirical and systematic research on this issue. The paper offers a quantitative and qualitative analysis and assessment of the content posted and major strategies used by opioid drug dealers on social media. Abstract: Fentanyl sale is often promoted on social media, but there is very little empirical and systematic research on this issue. This study attempts to fill a gap in the literature by utilizing big data and computational as well as qualitative analyses to better understand this phenomenon. The study's sample includes a unique dataset of over 6 million tweets and Instagram posts referencing fentanyl including 5687 messages (856 tweets and 4831 Instagram posts) that promoted fentanyl sale and provided some instructions on where and how to purchase it. From a theoretical point of view, it discusses the concept of Dark Social Networking Sites (DSNS) by building and expanding on the previous literature on dark social media. Second, it offers an assessment of the content posted and major strategies used by opioid drug dealers on social media which mostly involve exchanging contact information of mobile communication apps in order to arrange for money transfers and deliveries.